Pelatihan Praksis Konseling Adiktif untuk Meningkatkan Kompetensi Pedagogi dan Profesional Guru Bimbingan dan Konseling - Mudhar, Mudhar; muwakhidah, muwakhidah; Mufidah, Elia Firda; Moesarofah, Moesarofah (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2024)
Counseling is professional assistance provided by a counselor to a counselee. In a counseling relationship, personal qualities required by the counselor include empathy, congruence and respect. Counseling covers all aspects of life, one of which is addiction counseling. Counselors need to understand addiction counseling, namely so that the counselor has the goal of understanding behavior, motivations and knowing the feelings of the client, this goal is not limited to understanding the client. Counselors who already understand addiction counseling in helping the counselee's recovery, namely by knowing the counselee's self-understanding through group therapy (group counseling) and individual counseling which is a counseling activity that attempts to change the resident's behavior while undergoing the program. By providing addiction counseling practices, it can also be used to increase the personality competence of guidance and counseling teachers. In an effort to improve this competency, the guidance and counseling study program at PGRI Adi Buana University Surabaya provides community service related to the practice of addiction counseling to school counselors in the MGBK (Guidance and Counseling Teachers' Conference) at the SMP/MTs level. in Sidoarjo Regency, East Java